Livelihood Dilemma of The Rural Household Around The Oil Palm Plantation in East Kalimantan - Yulian, B.E.; Dharmawan, A.H.; Soetarto, E.; Pacheco, P. (Department of Communication and Community Development Sciences, 2012)
ABSTRACT The expansion of oil palm plantation is a necessity in Indonesia. The global market demand pressure and the need to accelerate national economic growth have supported the occurrence of massively expansion of oil palm plantation in Indonesia. Although it contributes many benefits from the economic side, but in another side, the oil palm plantation also gives social and environmental impacts. Such impacts are, among others, such as the changes of agrarian structure, land dispute, livelihood system of rural household, lack of biodiversity, crop monoculturalization, and deforestation. This research is aimed to describe socio-economic impacts caused by the expansion of oil palm plantation toward the livelihood system of rural household. By using livelihood survey and deep interview, this research obtains a fact that the oil palm plantation has, as if, provided prosperity for the rural household, but what really happens is high process of livelihood vulnerability and dependency toward income gained from the salary in oil palm plantation. Keywords: Oil palm, livelihood, dependency, and vulnerability ABSTRAK Ekspansi perkebunan kelapa sawit merupakan suatu keniscayaan bagi Indonesia. Tekanan permintaan pasar global dan kebutuhan untuk memacu pertumbuhan ekonomi nasional mendorong terjadinya ekspansi perkebunan kelapa sawit secara masif di Indonesia. Meskipun memberikan manfaat dari sisi ekonomi, di sisi lain perkebunan kelapa sawit juga memberi dampak sosial dan lingkungan. Dampak tersebut diantaranya seperti perubahan struktur agraria, sengketa lahan, sistem nafkah rumah tangga pedesaan, berkurangnya biodiversitas, monokulturisasi tanaman, hingga deforestasi. Penelitian ini bertujuan memberikan gambaran dampak sosial-ekonomi dari ekspansi perkebunan kelapa sawit bagi sistem nafkah rumah tangga pedesaan.Dengan menggunakan survey nafkah dan wawancara mendalam, penelitian ini mendapatkan fakta bahwa perkebunan kelapa sawit seolah memberikan kesejahteraan bagi rumah tangga pedesaan, namun yang terjadi adalah proses kerentanan dan ketergantungan nafkah yang tinggi terhadap pendapatan dari upah perkebunan kelapa sawit. Kata kunci: Kelapa sawit, nafkah, ketergantungan, dan kerentanan